Identificação e estimativa pesqueira de tubarões na costa de São Paulo (Província Argentina) utilizando marcadores genéticos - Ussami, Luis Henrique Fregadolli [UNESP] (2015)
Sharks and rays are currently among the most threatened vertebrate to extinction. This is due mainly to the fact that overfishing remains without effective control measures in almost the entire planet, including Brazil. Considering that each species responds independently to environmental pressures, and mainly to human actions, it is of fundamental importance for the development of appropriate management plans and programming the sustainable exploitation of these resources, to proceed to the characterization of local biodiversity, in the assessment of the species caught, in the correct identification of taxa and the most susceptible populations to fishing activities. However, especially for elasmobranches, such parameters are difficult to access, especially due to morphological similarities between species and also because of the fishing practice of removing parts such as the head and fins before landings, making it impossible to identify the most species. According elasmobranches capture records prepared by IBAMA in recent years, only about 20% of individuals receiving some identification indication, often only a popular name that can be related to more than one biological species, with the remainder fishing product classified just as sharks. The use of molecular tools in studies of the composition of biodiversity has provided its application in various areas, including in the identification of the species, in the study of their evolutionary relationships, and in assisting programs for their conservation. The use of molecular identification techniques as the PCR-multiplex type, and barcode sequences using part of the mitochondrial gene sequence Cytochrome Oxidase subunit I that permit to identify particular genetic characteristics of each taxon, are currently being used in the species recognition allowing simultaneous identification of different samples. In the present work, the objective of the study was to identify the species occurring...